Digital Citizenship in Omani Schools: Exploring the Integration of Digital Citizenship Dimensions by Social Studies Teachers in the Educational Context of Basic Education Schools - Alsaidi, Humaid Muslem; Albalushi, Fahad Abdullah; Alkaabi, Mohammed Said; Albirikia, Aysha Abdullah (Journal of Curriculum and Teaching Methodology, 2024)
The present study aimed to assess the extent to which social studies teachers in basic education schools in Oman incorporate the dimensions of digital citizenship within their instructional practices. Applying a descriptive research design, the researchers developed an observation card consisting of 30 phrases that represented three key dimensions: education, protection, and respect. Following the establishment of the card's validity and reliability. The findings revealed a moderate level of utilization of digital citizenship dimensions by social studies teachers in the classroom environment of basic education schools in the Sultanate of Oman.Moreover, the study identified statistically significant differences, at a significance level of α = 0.05, in the utilization of digital citizenship dimensions based on two variables. Firstly, gender emerged as a differentiating factor, with female teachers exhibiting a higher degree of integration compared to their male counterparts. Secondly, the variable of training demonstrated its influence, as teachers who had received training demonstrated a greater propensity for incorporating digital citizenship dimensions into their instructional practices. Based on these findings, the researchers advocate for the implementation of comprehensive training programs aimed at equipping teachers with the necessary knowledge and skills to effectively foster digital citizenship among students.
Keywords: digital citizenship; respect; education; protection